Islamic Education Values in Minangkabau Wedding Ceremony (Study of Traditional Mariage in Pauh, Padang, West Sumatera) - Al Furqan (AT-TA'LIM, 2016)
The aim of the research is to describe the processions of wedding ceremony that done by Pauh society. It also aims to find out whether the values of Islamic education are still carried out by the society in the wedding processions. The research was descriptive qualitative method using naturalistic approach where the data were obtained through observation and interview. The subjects of the research were the head of KAN Kerapatan Adat Nagari in Pauh, ninik mamak, cerdik pandai, the head of KUA, and religious leaders. Snowballing sampling technique was used and the head of the KAN of Pauh was decided to be the first key informant. Based on the information gathered from the key informants, it was found that Islamic education values were reflected in the procession of wedding ceremony. It is recommended that wedding ceremony in West Sumatra should be held properly based on the Isamic teaching.